Deciphering Smart Contracts, Legal Challenges, and Opportunities in Implementing Blockchain in the Property Sector in Indonesia - Robby Setiawan; Anwar Hidayat; Muhamad Abas (Universitas Labuhanbatu, 2024)
This research investigates the implementation of smart contracts in the Indonesian property sector, examining the legal opportunities and challenges involved. Blockchain technology offers high transparency, efficiency, and security in property transactions, but faces regulatory and infrastructural hurdles. The aim of this research is to explore the related legal dynamics, identify socio-economic impacts, and offer sustainable solutions. The research method employed is a qualitative legal approach to gather and analyze data. The findings indicate that although blockchain can expedite transaction processes and enhance transparency, the legal validity of smart contracts and consumer protection remain major issues. Regulatory updates and increased awareness of data security are necessary to optimize the adoption of this technology in Indonesia.Keywords: Blockchain., Property law., Regulation., Smart contracts., Transparency